SOSIALISASI DAN SIMULASI KEAMANAN SERVER KERBEROS DAN OPENLDAP DI SMK NEGERI 4 PALEMBANG - Lindawati; Fadhli, Mohammad; Soim, Sopian; Deta Mediana, Salwa (Politeknik Negeri Sriwijaya, 2024)
Computer networks are essential to daily life in the digital age because they link devices and provide distant information access. But technological progress also poses serious concerns to data security. Threats like viruses, malware, and hacker attacks put data's confidentiality and integrity in danger. For this reason, cybersecurity technicians must comprehend and use strong security frameworks. Kerberos, a security protocol that enables entities in a network to safely verify their identities, is one of the solutions that are presented. On the other side, directories are managed via Lightweight Directory Access Protocol (LDAP). In this context, teachers and students at the Vocational High School (SMK) with a focus on computer and network engineering receive instruction and training on network security. It is hoped that by doing this outreach, the community would see how important network security is and take the necessary precautions to safeguard data from intrusions. The outreach efforts were conducted at SMK Negeri 4 Palembang, which is the subject of this study. The findings demonstrate that students are able to test exploitation techniques on the framework used in the apache2 service and have a solid understanding of Kerberos, LDAP, and Firewalld.